(untitled) (Fiep Bulletin - online, 2019)
This scientific research had as a general objective to describe the motor development in volleyball practicing studentsof the Cristo Rei College. It is classified as a descriptive research of quantitative approach, due to its methodology being based onthe application of the test battery Korperkoordination Test furKinder - KTK. In this context, this study analyzed the influence ofvolleyball in the motor development process in 30 students aged 10 to 17 years practicing volleyball of the Cristo Rei Collegethrough the battery of KTK tests. Whose data were tabulated T-Student and parsed in Microsoft Office Excel. The result of thesample showed 33.3% of the students with insufficient coordination, 10% of the students had coordination problems, 26.6% ofthe students with normal coordination, 13.33% with good coordination and only 16.7% with excellent coordination. With this, itwas possible to observe that the largest population of the sample had a motor insufficiency due to being at the beginning of sportspractice, besides the lack of training and exercises that work with the development of their motor skills. It becomes necessary, thepractice of physical and sports activities such as volleyball, that allow the improvement of the motor coordination, andconsequently the promotion of the quality of life of these children.